DERMATOLOGY CASE - Falcão, Inês; Guerra, Isabel Couto; Horta, Miguel (BIRTH AND GROWTH MEDICAL JOURNAL, 2017)
Nevus spilus is a melanocytic lesion which can be congenital or develop early in life. This lesion varies considerably in size and can occur anywhere on the body. Although nevus spilus is benign, it has malignant potential and melanoma develops in rare cases. Prevention and early detection are mandatory. We describe the case of a nine-year-old boy with a nevus spilus.